Ta`'zir bi Ihlakil Mal Dalam Perspektif Wahbah Zuhayli: Suatu Analisis Terhadap Kitab Fiqh Islam wa Adillatuh - Jufri Yahya; Nazaruddin Nazaruddin; Abdurrazak Abdurrazak (Ma'had Aly Raudhatul Ma'arif, 2023)
This study, titled Ta’zir bi Ihlakil Mal According to Wahbah Zuhayli in the Book of Fiqh al-Islamiah wa Adillatuh in the Chapter on Ta’zir, aims to foster a peaceful, orderly, obedient, and consistent life in accordance with religious teachings, while avoiding conflicts, disputes, and bloodshed. To achieve this, Allah SWT has set specific laws and promises rewards for obedience, along with punishments for disobedience. The research focuses on two main issues: 1) What is the legal stance on ta’zir bi ihlakil mal according to Wahbah Zuhayli in Fiqh al-Islamiah wa Adillatuh in the chapter on ta’zir? and 2) What is the relevance of implementing ta’zir bi ihlakil mal in modern society according to the book? This study uses a qualitative research method with a normative legal approach. The findings conclude that, according to the majority of scholars from the Maliki, Hanbali, and other schools of thought, the punishment of ta’zir bi ihlakil mal is permissible under Islamic law, and wealth can be destroyed if it becomes a means of causing corruption. Additionally, ta’zir remains relevant in modern times as it is part of the Maqashid Syar'iyyah, just like other Islamic laws.